Fløjlshandskens politik. Færgen Storebælts kapring 1944 og den tyske gengældelsesaktion - Lauridsen, John T. (Historisk Tidsskrift, 2022)
The Hijack of the Ferry “Storebælt” in November 1944 and the Soft German Retaliation From November 1942 until May 1945, the German occupation of Denmark under the supervision of German Plenipotentiary Werner Best followed a logic that differed markedly from German policy in other occupied countries of Europe. Best took care always to have a Danish negotiating partner, even after the Danish government resigned in August 1943. The groundwork was Denmark’s exceptional status as a friendly nation after the implied Danish acceptance, under formal protest of course, of German occupation in April 1940. Best arrived in Denmark in November 1942, entrusted with the duty of maintaining the peace and stability that was a precondition for the vital Danish supply of foodstuff to Germany. On principle, this did not differ from the policy of his predecessor, Cecil von Renthe-Fink, but Best had to accomplish the task under conditions of mounting popular resistance, including wave upon wave of strikes, sabotage and general disorder. Best coped with these challenges without escalating the situation. He successfully mediated between German and Danish interests, thus maintaining the policy of collaboration by all available means. His handling of the hijack of the ferry “Storebælt” in November 1944 is a prime example. The hijacking to Sweden by the Danish resistance movement was a humiliation for the German Navy because a navy vessel had accompanied the ferry on its route. The German Navy insisted on retaliation. Best was forced to try to make the Swedish government return the ferry, but in vain. The German response was to confiscate a number of Danish vessels. However, through skilful maneuvering, in the eyes of the Danish government and public, Best made it appear as if it was not, in fact, a retaliatory measure but simply contingent on urgent necessities of the German war effort. A clear indication of Best’s success is the fact that in spite of their knowledge to the contrary, both the German Navy and the German Foreign Office in Berlin accepted his stunt.